Evidence of Predictable Behavior of Security Returns - JEGADEESH, NARASIMHAN (Journal of Finance, 1990)
ABSTRACT This paper presents new empirical evidence of predictability of individual stock returns. The negative first‐order serial correlation in monthly stock returns is highly significant. Furthermore, significant positive serial correlation is found at longer lags, and the twelve‐month serial correlation is particularly strong. Using the observed systematic behavior of stock returns, one‐step‐ahead return forecasts are made and ten portfolios are formed from the forecasts. The difference between the abnormal returns on the extreme decile portfolios over the period 1934–1987 is 2.49 percent per month .